ChemInform Abstract: Recent Advances in Water/Alcohol‐Soluble π‐Conjugated Materials: New Materials and Growing Applications in Solar Cells. Issue 5 (4th February 2014) - Duan, Chunhui; Zhang, Kai; Zhong, Chengmei; Huang, Fei; Cao, Yong
Abstract Review: 256 refs.